Pengaruh Daya Tarik, Kepercayaan Dan Keahlian Celebrity Endorser Terhadap Keputusan Pembelian Produk Scarlett Whitening (Studi Kasus Pada Masyarakat Kecamtan Dampit) - Nurul Muttamimah; Muhammad Ridwan Basalamah; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2022)
AbstractThe purpose of this study was to analyze the effect of attractiveness, trust and expertise of celebrity endorsers on purchasing decisions of Scarlett Whitening products. This study uses accidental sampling research using a quantitative approach. Sampling technique and population using non-probability sampling technique. Sources of data used in this study is primary data. Respondents in this study were the people of Dampit District. The number of respondents is 85 people. The analytical technique used in this research is multiple linear regression. Based on the results of research analysis, the variables of attractiveness, trust, and expertise have a simultaneous effect on purchasing decisions. There is a partial effect of attractiveness, trust, and expertise variables on purchasing decisions Keywords: Attractiveness, Trust, Expertise, Purchase Decision.